Daniel Ellsberg, Pentagon Papers whistleblower who exposed Vietnam War secrets, dies at 92 - News Wires (France 24, 2023)
Daniel Ellsberg, the U.S. military analyst whose change of heart on the Vietnam War led him to leak the classified "Pentagon Papers," revealing U.S. government deception about the war and setting off a major freedom-of-the-press battle, died on Friday at the age of 92, his family said in a statement.
United States of America
Keywords: 2023-06 June